Study of the ionic strength effect on the migration of polyamide 6 and 66 oligomers into liquid simulants by a LC-qTOF-MS method. (March 2023) - Tsochatzis, Emmanouil D.; Lopes, Joao Alberto; Kappenstein, Oliver
Abstract: Polyamides (PAs) are types of polymers used as food contact materials (FCMs) and articles such as kitchen utensils and packaging material. While caprolactam is an EU regulated substance and monomer of PA, this material's oligomers are instead considered as non-intentionally added substances (NIAS) and are typically found in PA-based packaging. An analytical methodology was developed and validated for the quantification of both monomers and oligomers of PA in official liquid food simulant (simulant A;10% v/v ethanol), using a quadruple time-of-flight mass spectrometer (QTOF-MS). The method was applied in the evaluation of the effect of the ionic strength on the migration of all the studied monomers and oligomers from a PA/polyethylene FCM multilayer film. The migration experiments results at different conditions (temperature, time) and with different concentration (% w/v) of NaCl, showed ranging values for the PA6 oligomers (trimer up to heptamer) and caprolactam. It was observed that in the presence of salt, the mass fractions of the migrated caprolactam, were above the limits specific in the respective EU regulation. Preliminary results seem to suggest that migration testing should consider not only the fatty content of a food, but also its salt content, as changes in the ionic strength may influence the migration of polar substances. Highlights: Validated method for PA6/PA66 monomers and oligomers analysis. Quantification of migrating PA6/PA66 monomers and oligomers. Migration study on real PA film. Migration levels may be affected by salinity of the food. Migration affected by exposure temperature and time.